Valo Bratina - Kocjančič, Ana (Amfiteater (Ljubljana), 2020)
The collection of the Slovenian Theatre Institute preserves the legacy of actor, director and set designer Valo Bratina (1887-1954) with an extensive map of his architectural plans and sketches for the construction of workers' and amateur theatres and stages in Ljubljana and Kočevje as well as in the Slovenian countryside. The map also contains some scenic drafts for his amateur performances. His designs include the renovation or redevelopment of the stages of Sokolski dom in Zagorje, Enotni sindikati in Ljubljana, Sindikalni oder in Trbovlje, Šeškov dom in Kočevje, as well as the designs for the façade and stage of Dom kulture in Hrastnik and the architectural project for the entire building, hall and stage of the Društveni dom in Štore. Since the Ljudska prosveta set forth the building standards for stages only in 1951, he had to develop some of his own solutions. He chose the form for the new amateur stages leaning on historical, naturalistic box stage with flats, which he based on his own proportions using some stage examples from literature. This article introduces the unknown period of Valo Bratina's work for the workers' and amateur stages in Slovenia from the end of World War II until his death in 1954.
Keywords: amaterska predstava; amaterski oder; amateur performance; an amateur stage; Bratina, Valo; gledališče; gledališka arhitektura; scenografija; scenography; theater architecture; theatre